2009
DOI: 10.1007/s11274-009-9986-5
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of milbemycin-producing Streptomyces bingchenggensis by rational screening of ultraviolet- and chemically induced mutants

Abstract: Milbemycin antibiotics are produced by Streptomyces hygroscopicus subsp. aureolacrimosus and a newly isolated Streptomyces bingchenggensis, respectively. According to the biosynthetic pathway of milbemycins generated by S. hygroscopicus subsp. aureolacrimosus, a rational screening procedure with UV irradiation and N-methyl-N 0 -nitroso-N-nitrosoguanidine (NTG) mutation was performed to obtain high milbemycin-producing S. bingchenggensis. Aminoacetic acid (Glycine)-resistant mutants (AA r ), propionate-resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 26 publications
0
12
0
2
Order By: Relevance
“…Proton Carbon In compound 1, the large J (14.6 Hz) of H-10 and H-11 and the NOESY crossing peaks (Figure 1) between H 2 -27 and H-10, H 3 -29 and H 2 -16 indicated that the three double bonds at C-8 and C-9, C-10 and C-11, C-14 and C-15 were E. The NOESY correlations of H-17, H 3 -30 and H-25, H-17 and H-19, H-11 and H 3 -28 suggested that these protons having the same orientations as in milbemycin b 12 .…”
Section: ) Secomilbemycins E (2) and F (3) (Coupling Constants In Pamentioning
confidence: 95%
See 1 more Smart Citation
“…Proton Carbon In compound 1, the large J (14.6 Hz) of H-10 and H-11 and the NOESY crossing peaks (Figure 1) between H 2 -27 and H-10, H 3 -29 and H 2 -16 indicated that the three double bonds at C-8 and C-9, C-10 and C-11, C-14 and C-15 were E. The NOESY correlations of H-17, H 3 -30 and H-25, H-17 and H-19, H-11 and H 3 -28 suggested that these protons having the same orientations as in milbemycin b 12 .…”
Section: ) Secomilbemycins E (2) and F (3) (Coupling Constants In Pamentioning
confidence: 95%
“…12 The culture temperature was 28 1C and the initial pH was 7.40 sterilized by sparging with steam at 121 1C for 30 min. The dissolved oxygen was maintained above 35% by adjusting the agitation speed.…”
mentioning
confidence: 99%
“…noncyanogenus and Streptomyces thermoarchaensis [16]. Apart from the mentioned strains, another newly milbemycin-producing strain Streptomyces bingchenggensis was isolated by our research team and currently used as an industrial producer of milbemycins [17]. S. bingchenggensis produces milbemycins A3/A4, two α-class milbemycins (B2/B3) and two β-class milbemycins (β 1 /β 2 ) as its major components together with the polyether ionophore nanchangmycin and a trace of new milbemycin analogs, including α 28 , α 29 , α 30 , β 13 , β 14 , ST906, and secomilbemycins A and B [18,19].…”
Section: Acaricidal and Nematocidal Capacitiesmentioning
confidence: 99%
“…Аналіз сучасних методів та прийомів в селекції мікробних продуцентів біологічно активних речовин свідчить про важливе значення гено типу вихідного штаму для отримання над продуцентів, а також про доцільність багатостадійної обробки культури послідовно різними типами мутагенів [2][3][4].…”
Section: аналіз літературних даних та постановка завданняunclassified
“…Так, використання УФ випромінювання дало змогу отримати надпродуценти родів Bacillus та Coniothyrium з підвищеним у 2-10 разів рівнем біосинтезу фермен тів [5,6], cтупінчаста обробка УФ випромінюванням та хімічними мутагенами стала ефективною в селекції продуцентів антибіотиків та ферментів родів Streptomyces, Pseudomonas та інших [3,4].…”
Section: аналіз літературних даних та постановка завданняunclassified